APPLICATION OF THE ENTROPY-PROBABILISTIC MODEL OF THE X-RAY TELEVISION INTROSCOPE OPERATOR IN THE ALGORITHM OF THE COMPUTER SIMULATOR DURING TRAINING OF SECURITY SCREENING POINT EMPLOYEES - A. K. Volkov; V. V. Iudaev; A. V. Dormidontov (Научный вестник МГТУ ГА)
The article discusses the possibility of applying the entropy-probabilistic model of the operator x-ray television introscope in the algorithm of the computer simulator in order to increase the effectiveness of professional training of employees of the aviation security service employees. The model is based on a stochastic representation of the system “operator” in the form of multi-dimensional random vector, each component of which is a random continuous value, describing the probability of dangerous goods detection forbidden for transportation by air transport. The main advantages of the proposed approach are as follows:ease of implementation and interpretation of the operator entropy model;entropy model, realized in specific algorithm, is applicable for diagnostic tasks and stochastic system “operator” control and also for effective management in the learning process.